South Africa’s (Possible) Withdrawal from the ICC and the Future of the Criminalization and Prosecution of Crimes Against Humanity, War Crimes and Genocide Under Domestic Law: A Submission Informed by Historical, Normative and Policy Considerations - Gerhard Kemp (Washington University Global Studies Law Review, 2017)
The ANC-led Government’s decision in October 2016 to withdraw South Africa from the International Criminal Court (“ICC”) came as a shock to those who regard South Africa as a champion of international criminal justice on the African continent. The decision was vehemently opposed by opposition parties and civil society in South Africa. The high court in Pretoria ultimately annulled South Africa’s notice of withdrawal from the ICC, and the ICC Repeal Bill was also withdrawn from the parliament. This Article argues for South Africa’s continued membership of the ICC. The argument is informed by the history and traditions of the ANC, an internationalist liberation movement-turned-government and one of the early supporters of the ICC. The Article explores the normative roots of the ANC’s commitment to accountability for serious violations of human rights and humanitarian law, not only via the ICC, but also via incorporation of international criminal law in South African domestic criminal law. While the Article does not pretend to know the political fate of the ANC-led Government’s future attitude to the ICC, it is argued that there are solid normative foundations on which the ANC should build to advance the project to end impunity for the worst crimes under international law.
Keywords: South Africa; International Criminal Court; Rome Statute; Democratic Alliance v. Minister of International Relations and Cooperation and Others; Constitutional Law; Criminal Law; National Commissioner of the South African Police Service v. Southern African Human Rights Litigation Centre & Another; International Law; Human Rights; African National Congress